Aksi Kerelawanan: Meningkatkan Pengetahuan & Sikap Kesiagaan Isu Bencana Melalui Video Edukasi Di Beneran Indonesia - Kinanti Putri Herlambang; Radysti Devania (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Indonesia is a country that has a high potential for natural disasters. This is because Indonesia is located in the ring of fire which forms an archipelago. Program from Beneran Indonesia in the form of Service Learning (SL) is a volunteer action carried out to increase the effectiveness of disaster prevention and mitigation by optimizing public awareness strategies so that community participation can increase in carrying out disaster prevention and mitigation, research and spatial and land planning. The form of this program is in the form of educational videos sent via social media, Instagram. The purpose of this research is to analyze the effectiveness of disaster education videos to increase disaster knowledge and attitudes in the community. With a qualitative descriptive analytic observation method with a cross sectional approach through data collection techniques in the form of observation and documentation. Thus, the results of this research also show that this disaster education video media is effective for increasing disaster knowledge and attitudes. Because the effective and efficient dissemination is accompanied by packaging of video content that is concise, solid and enjoyable.